Needle stick injuries in a tertiary care hospital in India: observations from a clinical audit - Gita, N.; Rao, N. P. (International Journal of Research in Medical Sciences, 2017)
Background: Needle stick injuries (NSI) is notably one of the most common and preventable occupational hazard amongst healthcare workers (HCW). This article reports the findings of a clinical audit for needle stick injuries (NSI) conducted at a tertiary care hospital, Pune, Maharashtra, India. Methods: Clinical audit was conducted at the 123 bed ISO 9002 certified and NABH accredited tertiary care hospital having safety protocols and incident reporting mechanisms in place. Data included all reported and unreported events of NSI. Information about the unreported events was collected through personal interview of all HCWs (99 men and 180 women) and employed doctors (23 men and 09 women). The nature of events and situations when NSI occurred were described. This being a only exploratory analysis is done. Results: With a total of 36,376 patients treated in the hospital during 2015, a total of 2,16,336 injections were given. Only 11 NSI events were documented during the year and all were reported voluntarily by the HCWs after the incident occurred. All events occurred in the HCWs and no doctors were involved in any of the NSI events. The number of NSI events per 1000 patients treated (IPD and OPD) was 0.302, i.e. 0.03%, and the annual incidence was 8.94% for the hospital beds. Female HCW’s (63.6%) were involved more in NSI than males (36.4%). Conclusions: Continuous education of all categories of HCWs plays a crucial role in capturing NSI. Staff should be encouraged to self-report without any delay and should treat each NSI as an emergency.